Removal rates and energy demand of the electrochemical oxidation of ammonia and organic substances in real stored urine - Zöllig, Hanspeter (Environ Sci (Camb), 2017)
The separate collection and treatment of urine allows for an environmentally friendly and cost-efficient management of the nutrients contained in urine. The primary goal should be to recover all these nutrients. However, in some cases it will be economically or ecologically more sensitive to recover only the phosphorus, while nitrogen is removed together with organic substances (measured as chemical oxygen demand, COD) and pathogens. In this study, we investigated the use of galvanostatic electrolysis for the removal of nitrogen and COD from real stored urine. Non-active type boron-doped diamond (BDD) and active type thermally decomposed iridium oxide film (TDIROF) anodes were evaluated using batch experiments. On both anodes, ammonia was exclusively removed by indirect oxidation with active chlorine (AC:Cl(2), HClO, and ClO(−)). As a consequence, ammonia was not completely removed, if chlorine was consumed by competing processes. While COD was present, ammonia removal was faster on TDIROF (227 ± 16 gN m(−2) d(−1) at 20 mA cm(−2)) than on BDD (43 ± 20 gN m(−2) d(−1) at 20 mA cm(−2)). The reason for the slower ammonia removal on BDD was the enhanced reaction of AC with organic molecules. In fact, hydroxyl radicals broke organic molecules down to shorter chain molecules which reacted with most of the AC leaving only little AC for the oxidation of ammonia. This preferential oxidation of organics resulted in very high COD removal rates on BDD (above 420 gCOD m(−2) d(−1) at 20 mA cm(−2) for COD concentrations above 1000 mgCOD L(−1)). A main drawback of electrolysis with both anodes was the high energy demand (BDD: 55 W h gCOD(−1) and 766 W h gN(−1) for 90% and 6% removal, respectively. TDIROF: 67 W h gCOD(−1) and 77 W h gN(−1) for 30% and 40% removal. All at 20 mA cm(−2)). It can be concluded that BDD and TDIROF anodes could be combined in series for a fast, complete, and more energy efficient electrochemical urine treatment: COD could be removed on BDD before the residual ammonia would be removed on TDIROF.